1994
DOI: 10.1183/09031936.94.07071342
|View full text |Cite
|
Sign up to set email alerts
|

Chronic lung diseases and the perception of breathlessness: a clinical perspective

Abstract: Breathlessness is an extremely common symptom. Its genesis is incompletely understood but is known to be largely determined by many of the mechanical factors associated with the act of breathing. As with all subjective sensations various other factors including volition, behavioural style and other cortical and subcortical factors play a part in its genesis.The relief of breathlessness is primarily directed at the underlying disorder. In those conditions and situations where specific therapy has little to offe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 55 publications
0
19
1
Order By: Relevance
“…Downgrading of the sensory experience is consistent with the phenomenon of temporal adaptation. It is reasonable to believe that such downgrading takes a significant length of time, but this has not yet been defined [30]. This could explain the difference between the results of Burdon et al [1] and the present ones.…”
Section: Discussioncontrasting
confidence: 77%
“…Downgrading of the sensory experience is consistent with the phenomenon of temporal adaptation. It is reasonable to believe that such downgrading takes a significant length of time, but this has not yet been defined [30]. This could explain the difference between the results of Burdon et al [1] and the present ones.…”
Section: Discussioncontrasting
confidence: 77%
“…The decrease in lung function in patients with COPD (and to some extent in patients with asthma) is gradual during their lives. Due to patients adapting to this gradual decrease [7][8][9] or due to the doctor not being aware of the symptoms and risk factors, COPD is often diagnosed late in its course [4,7]. In the developing world, lack of resources, diagnostic facilities and physicians working on a community level, often constitute an even greater obstacle in establishing an early diagnosis.…”
mentioning
confidence: 99%
“…This perception is modulated by past experience: the brain seems to memorize the level and the characteristics/quality of dyspnea induced by a previous activity, effort, or situation, to set the expectations accordingly, and ultimately compare the current input with that in the past [52,53]. It has been shown that, following conditioning, even harmless cues per se may trigger dyspnea with varying susceptibilities in different groups of individuals [54].…”
Section: Neurophysiologymentioning
confidence: 98%